Implementasi Penguatan Kapasitas Kerjasama Indonesia-United States Agency For International Development (USAID) Dalam Bidang Pendidikan - Dewi Romantika Tinambunan; Esra Natasya Sitepu; Ivana Theo Philia; Jekson Saragih; Laras Sati Sintania; Ture Ayu Situmeang; Isnaniah Isnaniah (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2023)
International cooperation is a form of cooperation carried out by a country with other countries across its territorial borders. The aim of cooperation is to meet the needs of the country. This research is entitled "implementation of strengthening the capacity of cooperation between Indonesia and the United States Agency for International Development (Usaid) in the field of education". This research was carried out with the aim of finding out the relationship between Indonesia and USAID in the field of education. The method used in this research is a qualitative approach literature study research method. This research produces insight into how Indonesia's collaboration with USAID has had a positive impact in the world of education.